A Power Sharing Method for Parallel Inverters with Virtual Synchronous Generator Control Strategy - Sara Yahia Altahir Mohamed; Xiangwu Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
A new power sharing method of a virtual sychronous generator control based inverters is introduced in this paper. Since virtual synchronous generator has virtual inertia and damping properties, it significantly enhances the grid stability. However, its output power considerably affects by the line impedance. Thus, in this paper, the relation between the droop control and the line impedance is analyzed at first. Then, by appling an improved droop control strategy to an inverter based on the virtual sychronous generator control, achieving proportional active and reactive power sharing unaffected by the line impedance is realized. The result shows that a smooth response is achieved. As well as, the voltage drop caused by the line impedance is totally compensated. As a result, the system stability is furtherly improved. At last, the effectiveness of the proposed method is verified through MATLAB/Simulink.